Peran social media specialist dalam membangun brand awareness nimo tea resort di instagram - Fadilla, Rashina Zahra; Burhanuddin; Burhani , Al - May Abyan Izzy; Firdaus, Diky (Universitas Garut, 2026)
Abstract The advancement of digital technology has encouraged companies across sectors, including the hospitality industry, to maximize social media as a platform for building brand image and strengthening consumer engagement. Instagram becomes the main medium for Nimo Tea Resort to showcase its visual advantages and increase brand awareness. However, the high follower count is not aligned with interaction levels, indicating the need for deeper analysis of the social media specialist’s role in managing the @nimotea_resort account. This study aims to examine the strategies and responsibilities of the social media specialist in planning, producing, optimizing, and evaluating Instagram content to build brand awareness. Using a descriptive qualitative method through interviews, observation, documentation, and literature review, the research adopts Regina Luttrel’s (2022) Circular Model of SoMe, which includes the stages of share, optimize, manage, and engage. The findings show that the social media specialist holds a key role in aligning trends with the resort’s identity, maintaining consistent visuals, responding to the audience in real time, and forming collaborations to broaden reach. Nonetheless, interaction remains low due to algorithmic shifts, rapid trend changes, and challenges in harmonizing trends with the brand’s elegant and exclusive tone. This study enriches digital communication research in hospitality and offers practical recommendations for strengthening Nimo Tea Resort’s visual-based social media strategies. Keywords: Brand awareness; instagram; social media management; social media marketing. Abstrak Perkembangan teknologi digital mendorong semua bidang perusahaan termasuk salah satunya bidang hospitality untuk memaksimalkan media sosial sebagai sarana membangun citra dan membangun interaksi dengan konsumen. Instagram menjadi platform utama yang dimanfaatkan Nimo Tea Resort untuk menampilkan keunggulan visual dan memperkuat brand awareness. Namun, tingginya jumlah pengikut tidak sebanding dengan tingkat interaksi, sehingga diperlukan analisis mendalam mengenai peran Social media specialist dalam pengelolaan akun @nimotea_resort. Penelitian ini bertujuan menganalisis strategi dan peran social media specialist dalam merencanakan, memproduksi, mengoptimalkan, serta mengevaluasi konten Instagram guna membangun brand awareness. Penelitian menggunakan pendekatan kualitatif deskriptif melalui wawancara, observasi partisipatif, dokumentasi, dan studi pustaka, dengan analisis data tematik berbasis teori The Circular Model of Some oleh Regina Luttrel (2022) yang mencakup tahap share, optimize, manage, dan engage. Hasil penelitian menunjukkan bahwa social media specialist berperan penting dalam menyesuaikan tren dengan karakter resort, menjaga konsistensi visual, merespons audiens secara real time, serta menjalin kolaborasi sebagai upaya memperluas jangkauan. Namun, interaksi belum optimal karena tantangan algoritma, perubahan tren yang cepat, serta keterbatasan kesesuaian tren dengan brand voice. Penelitian ini berkontribusi dalam memperkaya kajian komunikasi digital pada sektor hospitality serta memberikan rekomendasi praktis bagi Nimo Tea Resort dalam membangun efektivitas strategi media sosial berbasis visual untuk memperkuat brand awareness. Kata-kata kunci: Kesadaran merek; Instagram; manajemen media sosial; pemasaran media sosial.